Optical filter and method for manufacturing the same

JP2024059822A5Pending Publication Date: 2025-03-21NIPPON SHEET GLASS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024026307
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-04-18
Filing Date
2024-02-26
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing optical filters in imaging devices face challenges in achieving desired flexibility in their light absorption layers, leading to issues such as cracking, wrinkling, and difficulty in handling and integration with sensors due to the rigidity of the light absorption layer materials.

Method used

A light-absorbing composition containing a light absorber, curable resin, and alkoxysilane, particularly dialkoxysilane, is used to form a light absorption layer with a Young's modulus of 2.00 GPa or less and hardness of 0.06 GPa or less, allowing for enhanced flexibility and resistance to mechanical deformation.

Benefits of technology

The composition imparts desired flexibility to the light absorption layer, reducing the likelihood of cracking and chipping during handling and integration, while maintaining effective light absorption properties, even under thermal expansion and contraction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000019_0000
    Figure 00000019_0000
  • Figure 00000019_0001
    Figure 00000019_0001
  • Figure 00000019_0002
    Figure 00000019_0002
Patent Text Reader

Abstract

To provide a light-absorbing composition which is advantageous for providing a desired flexibility to a light absorbing layer of an optical filter.SOLUTION: The light-absorbing composition of the present invention includes a light-absorbing agent, a curable resin, and alkoxysilane. The alkoxysilane includes dialkoxysilane. Since the alkoxysilane of the light-absorbing composition includes dialkoxysilane, it becomes easier to provide a desired flexibility to a light-absorbing layer by an organic functional group of dialkoxysilane while forming a strong bone structure having a siloxane bond in the light absorbing layer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to light absorbing compositions and optical filters. [Background technology]

[0002] In an imaging device using a solid-state imaging element such as a CCD (Charge Coupled Device) or a CMOS (Complementary Metal Oxide Semiconductor), various optical filters are arranged in front of the solid-state imaging element in order to obtain an image with good color reproducibility. In general, a solid-state imaging element has a spectral sensitivity in a wide wavelength range from the ultraviolet region to the infrared region. Meanwhile, human visual sensitivity exists only in the visible light region. For this reason, a technique is known in which an optical filter that blocks part of infrared or ultraviolet light is arranged in front of the solid-state imaging element in order to bring the spectral sensitivity of the solid-state imaging element in the imaging device closer to the human visual sensitivity.

[0003] Conventionally, such optical filters generally use light reflection by a dielectric multilayer film to block infrared or ultraviolet rays. Meanwhile, in recent years, optical filters with a film containing a light absorbent have been attracting attention. The transmittance characteristics of an optical filter with a film containing a light absorbent are not easily affected by the angle of incidence, so that even if light is obliquely incident on the optical filter in an imaging device, a good image with little change in color can be obtained. In addition, a light-absorbing optical filter that does not use a light-reflecting film can suppress the occurrence of ghosts and flares caused by multiple reflections by the light-reflecting film, so that good images can be easily obtained in backlit conditions or when photographing night scenes. In addition, an optical filter with a film containing a light absorbent is also advantageous in terms of miniaturizing and thinning the imaging device.

[0004] For example, Patent Document 1 describes an optical filter having a UV-IR absorbing layer capable of absorbing infrared and ultraviolet rays. The UV-IR absorbing layer contains a UV-IR absorbent formed of phosphonic acid and copper ions. Patent Document 2 describes an infrared cut filter having an organic dye-containing layer and a copper phosphonate-containing layer. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 6232161 [Patent Document 2] Patent No. 6281023 Summary of the Invention [Problem to be solved by the invention]

[0006] The techniques described in Patent Documents 1 and 2 have room for reexamination from the viewpoint of imparting a desired flexibility to a light absorbing layer in an optical filter. Therefore, the present invention provides an advantageous light absorbing composition from the viewpoint of imparting a desired flexibility to a light absorbing layer in an optical filter. The present invention also provides an optical filter having a light absorbing layer with a desired flexibility. [Means for solving the problem]

[0007] The present invention relates to A light absorbing agent; A hardening resin; An alkoxysilane, The alkoxysilane includes a dialkoxysilane. A light absorbing composition is provided.

[0008] The present invention also provides an optical filter comprising a light absorbing layer formed from a cured product of the above light absorbing composition.

[0009] The present invention also provides a method for producing a method for manufacturing a semiconductor device comprising the steps of: A light absorbing layer containing a light absorber and a hydrolysis condensate of an alkoxysilane, When one main surface of the light absorbing layer is measured according to a nanoindentation method (continuous stiffness measurement method) using a nanoindenter, the average Young's modulus is 2.00 GPa or less and the average hardness is 0.06 GPa or less. An optical filter is provided. Effect of the Invention

[0010] The light absorbing composition is advantageous in terms of imparting a desired flexibility to the light absorbing layer in the optical filter. Also, the light absorbing layer of the optical filter has the desired flexibility. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a cross-sectional view showing an example of an optical filter according to the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing another example of the optical filter according to the present invention. [Diagram 3] FIG. 3 shows the transmittance spectrum of the optical filter according to the first embodiment. [Figure 4] FIG. 4 shows the transmittance spectrum of the optical filter according to the second embodiment. [Diagram 5] FIG. 5 shows the transmittance spectrum of the optical filter according to the third embodiment. [Figure 6] FIG. 6 shows the transmittance spectrum of the optical filter according to Comparative Example 1. As shown in FIG. [Figure 7] FIG. 7 shows the transmittance spectra of the optical filter according to Example 1 before and after the humidity resistance test. [Figure 8] FIG. 8 shows the transmittance spectra of the optical filter according to Example 2 before and after the humidity resistance test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] As optical filters with a light absorbing layer, there are two types: an optical filter that is composed of a single light absorbing layer, and an optical filter that has a light absorbing layer formed on a substrate such as glass or resin. In the case of the former type of optical filter, if the light absorbing layer is hard or has a high hardness like glass, the flexibility of the light absorbing layer is likely to be low, and for example, when the optical filter is bent or mechanically deformed, the light absorbing layer may crack or wrinkle. In the case of the latter type of optical filter in which the light absorbing layer is formed on a substrate having flexibility such as resin, the light absorbing layer may crack or wrinkle when the optical filter is similarly deformed. For this reason, these optical filters must be handled with great care.

[0013] In the manufacturing process, when cutting a large-area optical filter to produce chips, equipment for cutting glass, such as a large slicer, is required. In addition, when cutting an optical filter, it may be necessary to consider cracking or chipping, which is a problem associated with the nature of glass materials. Furthermore, if an optical filter is hard when attempting to place and bond an optical filter on a sensor such as a solid-state imaging device, it may be difficult to place and bond the optical filter due to the inherent warping (unevenness in flatness) of the optical filter. In order to facilitate such processing, it is advantageous to increase the flexibility of the light absorbing layer.

[0014] Therefore, the present inventors have been researching day and night to find an advantageous technique from the viewpoint of imparting the desired flexibility to the light absorbing layer, and have devised the light absorbing composition and optical filter according to the present invention.

[0015] Hereinafter, embodiments of the present invention will be described. Note that the following description is merely an example of the present invention, and the present invention is not limited to these.

[0016] The light absorbing composition according to the present invention contains a light absorbing agent, a curable resin, and an alkoxysilane. In addition, the alkoxysilane contains a dialkoxysilane.

[0017] When a light absorbing layer is formed using the light absorbing composition, silanol groups are generated by hydrolysis of alkoxysilane. Compounds derived from alkoxysilane having the generated silanol groups are further reacted and polycondensed to form a strong skeleton having a siloxane bond (-Si-O-Si-). If the organic component (organic functional group) in the substance having the skeleton is small, the light absorbing layer formed is unlikely to have the desired flexibility. In this case, when a strong pressure is applied locally to the light absorbing layer, the skeleton having the siloxane bond is easily broken. However, since the alkoxysilane of the light absorbing composition contains dialkoxysilane, the light absorbing layer is likely to be given the desired flexibility by the organic functional group of the dialkoxysilane while forming a strong skeleton having a siloxane bond in the light absorbing layer. For this reason, for example, when the light absorbing layer formed using the light absorbing composition is cut, cracks and chipping are unlikely to occur. In addition, even if the light absorbing layer formed using the light absorbing composition is bent, the light absorbing layer is unlikely to break.

[0018] For example, it is conceivable to provide an optical filter integrated with an imaging element or optical component by applying a light-absorbing composition onto a solid-state imaging element such as a CCD or CMOS or an optical component. When an optical filter integrated with an imaging element or optical component is placed in a predetermined heat cycle environment, thermal expansion and thermal contraction may occur. A light-absorbing layer formed using the light-absorbing composition is likely to have a desired flexibility and is likely to deform in response to thermal expansion and thermal contraction. Therefore, breakage and damage to the light-absorbing layer are likely to be suppressed.

[0019] Furthermore, a highly flexible optical filter can be fabricated as a filter with a flat surface, and then bent along a curved arrangement surface when incorporated into an optical system to form a curved surface. By making the main surface of the optical filter a curved surface, it can also be used to accommodate the design of special imaging devices that require complex sensor arrangements.

[0020] The dialkoxysilane is not limited to a specific dialkoxysilane. The dialkoxysilane has, for example, a hydrocarbon group having 1 to 6 carbon atoms bonded to a silicon atom. The alkoxysilane may have a halogenated hydrocarbon group in which at least one hydrogen atom in the hydrocarbon group having 1 to 6 carbon atoms bonded to a silicon atom is substituted with a halogen atom. In this case, the light absorbing layer formed using the light absorbing composition is further likely to be given the desired flexibility.

[0021] The dialkoxysilane may be, for example, an alkoxysilane represented by the following formula (b): In this case, the desired flexibility is more reliably imparted to the light absorbing layer formed using the light absorbing composition. (R2)2-Si-(OR3)2(b) [In the formula, each R2 is independently an alkyl group having 1 to 6 carbon atoms, and each R3 is independently an alkyl group having 1 to 8 carbon atoms.]

[0022] The dialkoxysilane may be, for example, dimethyldiethoxysilane, dimethyldimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, or 3-glycidoxypropylmethyldiethoxysilane.

[0023] In the light-absorbing composition, the alkoxysilane may further include at least one of a tetraalkoxysilane and a trialkoxysilane, which makes it easier for a dense structure to be formed by siloxane bonds in the light-absorbing layer formed using the light-absorbing composition.

[0024] In the light-absorbing composition, the alkoxysilane may further include a tetraalkoxysilane and a trialkoxysilane, which more reliably facilitates the formation of a dense structure by siloxane bonds in the light-absorbing layer formed using the light-absorbing composition.

[0025] In the light absorbing composition, the at least one of the tetraalkoxysilane and the trialkoxysilane is not limited to a specific alkoxysilane. For example, in the light absorbing composition, the alkoxysilane is at least one selected from the group consisting of tetramethoxysilane, tetraethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, n-propyltriethoxysilane, n-propyltrimethoxysilane, hexyltriethoxysilane, hexyltrimethoxysilane, trifluoropropyltriethoxysilane, trifluoropropyltrimethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, and 3-isocyanatepropyltrimethoxysilane.

[0026] The content of dialkoxysilane in the alkoxysilane is not limited to a specific value. The content of dialkoxysilane in the alkoxysilane is, for example, 15 to 48% by mass, calculated as a complete hydrolysis condensate of the alkoxysilane. This makes it easier to more reliably impart the desired flexibility to the light absorbing layer formed using the light absorbing composition.

[0027] The content of dialkoxysilane in the alkoxysilane is preferably 15 to 20% by mass, calculated as a complete hydrolysis condensate of the alkoxysilane. This allows the light absorbing layer formed using the light absorbing composition to exhibit high moisture resistance. This is because a dense structure is formed by the siloxane bond, and the light absorber is less likely to aggregate in a high humidity environment.

[0028] The light absorbing agent is not limited to a specific light absorbing agent as long as it can absorb light of a predetermined wavelength. The light absorbing agent may be formed, for example, of a phosphonic acid represented by the following formula (a) and a copper ion. [ka] [In the formula, R 11 is an alkyl group, an aryl group, a nitroaryl group, a hydroxyaryl group, or a halogenated aryl group in which at least one hydrogen atom in the aryl group is substituted with a halogen atom.

[0029] In the light-absorbing composition, for example, a phosphonic acid represented by formula (a) is coordinated to a copper ion to form a light absorber. Also, for example, fine particles containing at least a light absorber are formed in the light-absorbing composition. In this case, due to the action of alkoxysilane, the fine particles are dispersed in the light-absorbing composition without agglomeration. The average particle diameter of the fine particles is, for example, 5 nm to 200 nm. If the average particle diameter of the fine particles is 5 nm or more, no special process is required for finely granulating the fine particles, and the structure of the fine particles containing at least a light absorber is less likely to be broken. Also, the fine particles are well dispersed in the light-absorbing composition. Also, if the average particle diameter of the fine particles is 200 nm or less, the effect of Mie scattering can be reduced, the transmittance of visible light can be improved in the optical filter, and the deterioration of characteristics such as contrast and haze of the image captured by the imaging device can be suppressed. The average particle diameter of the fine particles is preferably 100 nm or less. In this case, the effect of Rayleigh scattering is reduced, so that the transparency to visible light is increased in the optical filter produced using the light-absorbing composition. The average particle size of the fine particles is more preferably 75 nm or less. In this case, the transparency of an optical filter produced using the light-absorbing composition to visible light is particularly high. The average particle size of the fine particles can be measured by a dynamic light scattering method.

[0030] Phosphate esters are sometimes used as dispersants for light absorbers. Therefore, the light absorbing composition may contain a phosphate ester. On the other hand, in a light absorbing layer formed using the light absorbing composition, a compound derived from an alkoxysilane can appropriately disperse the light absorber while imparting higher moisture resistance to the light absorbing layer compared to a phosphate ester. Therefore, the amount of phosphate ester used can be reduced by including an alkoxysilane in the light absorbing composition. In the formation of the light absorbing layer, the alkoxysilane present around the light absorber reacts with the dialkoxysilane, so that the light absorbing layer is homogeneous and tends to have high density. The light absorbing composition may not contain a phosphate ester.

[0031] The phosphate ester is, for example, a phosphate ester having a polyoxyalkyl group. The phosphate ester having a polyoxyalkyl group is not limited to a specific phosphate ester. The phosphate ester having a polyoxyalkyl group is, for example, Plysurf A208N: polyoxyethylene alkyl (C12, C13) ether phosphate ester, Plysurf A208F: polyoxyethylene alkyl (C8) ether phosphate ester, Plysurf A208B: polyoxyethylene lauryl ether phosphate ester, Plysurf A219B: polyoxyethylene lauryl ether phosphate ester, Plysurf AL: polyoxyethylene styrenated phenyl ether phosphate ester, Plysurf A212C: polyoxyethylene tridecyl ether phosphate ester, or Plysurf A215C: polyoxyethylene tridecyl ether phosphate ester. All of these are products manufactured by Daiichi Kogyo Seiyaku Co., Ltd. The phosphate ester may also be, for example, NIKKOL DDP-2: polyoxyethylene alkyl ether phosphate ester, NIKKOL DDP-4: polyoxyethylene alkyl ether phosphate ester, or NIKKOL DDP-6: polyoxyethylene alkyl ether phosphate ester. All of these are products manufactured by Nikko Chemicals Co., Ltd.

[0032] In the light absorbing composition, the curable resin is not limited to a specific resin. The curable resin is, for example, a silicone resin. The silicone resin is a compound having a siloxane bond in its structure. In this case, the hydrolysis polycondensate of alkoxysilane also has a siloxane bond, so that in the light absorbing layer formed by using the light absorbing composition, the hydrolysis polycondensate of alkoxysilane and the curable resin are compatible with each other.

[0033] The resin is preferably a silicone resin containing an aryl group such as a phenyl group. If the resin contained in the optical filter is hard (rigid), as the thickness of the layer containing the resin increases, cracks are likely to occur due to hardening shrinkage during the manufacturing process of the optical filter. If the resin is a silicone resin containing an aryl group, the layer formed by the light absorbing composition is likely to have good crack resistance. In addition, the silicone resin containing an aryl group has high compatibility with the phosphonic acid represented by formula (a) and is unlikely to aggregate the light absorber. Specific examples of silicone resins used as the matrix resin include KR-255, KR-300, KR-2621-1, KR-211, KR-311, KR-216, KR-212, KR-251, and KR-5230. All of these are silicone resins manufactured by Shin-Etsu Chemical Co., Ltd.

[0034] An example of a method for preparing a light absorbing composition will be described below, taking as an example the case where the light absorber is formed from the above-mentioned phosphonic acid and copper ions.

[0035] For example, the light absorbing composition may have the formula (a) represented by R 11In the case where the phosphonic acid (aryl phosphonic acid) is an aryl group, a nitroaryl group, a hydroxyaryl group, or an aryl halide group, the solution D is prepared as follows. A copper salt such as copper acetate monohydrate is added to a predetermined solvent such as tetrahydrofuran (THF) and stirred to prepare a solution A, which is a solution of the copper salt. Next, an aryl phosphonic acid is added to a predetermined solvent such as THF and stirred to prepare a solution B. When multiple types of aryl phosphonic acid are used as the phosphonic acid represented by formula (a), each aryl phosphonic acid may be added to a predetermined solvent such as THF and stirred to prepare multiple spare solutions prepared for each type of aryl phosphonic acid, to prepare the solution B. For example, an alkoxysilane is added in the preparation of the solution B. While stirring the solution A, the solution B is added to the solution A and stirred for a predetermined time. Next, a predetermined solvent such as toluene is added to this solution and stirred to obtain the solution C. Next, the solution C is heated and subjected to a desolvation treatment for a predetermined time to obtain the solution D. As a result, the solvent such as THF and the components generated by dissociation of the copper salt such as acetic acid (boiling point: about 118°C) are removed, and the light absorber is generated by the phosphonic acid represented by formula (a) and the copper ions. The temperature at which the C solution is heated is determined based on the boiling point of the components to be removed that are dissociated from the copper salt. In the desolvation process, the solvent such as toluene (boiling point: about 110°C) used to obtain the C solution also volatilizes. Since it is desirable that this solvent remains to some extent in the light absorbing composition, it is preferable that the amount of the solvent added and the time of the desolvation process be determined from this perspective. In addition, o-xylene (boiling point: about 144°C) can be used instead of toluene to obtain the C solution. In this case, since the boiling point of o-xylene is higher than that of toluene, the amount added can be reduced to about one-fourth of the amount added of toluene.

[0036] The light absorbing composition comprises a compound represented by formula (a) represented by R 11When the alkyl group of phosphonic acid (alkyl phosphonic acid) is contained, for example, the H solution is further prepared as follows. First, a copper salt such as copper acetate monohydrate is added to a predetermined solvent such as tetrahydrofuran (THF) and stirred to obtain a solution E of the copper salt. In addition, an alkyl phosphonic acid is added to a predetermined solvent such as THF and stirred to prepare the F solution. When multiple types of phosphonic acid are used as the alkyl phosphonic acid, each alkyl phosphonic acid may be added to a predetermined solvent such as THF and stirred to prepare the F solution by mixing multiple preliminary solutions prepared for each type of alkyl phosphonic acid. For example, an alkoxysilane is further added in the preparation of the F solution. While stirring the E solution, the F solution is added to the E solution and stirred for a predetermined time. Next, a predetermined solvent such as toluene is added to this solution and stirred to obtain the G solution. Next, the G solution is subjected to a desolvation treatment for a predetermined time while heating it to obtain the H solution. This removes the solvent such as THF and the components generated by the dissociation of the copper salt such as acetic acid. The temperature to which solution G is heated is determined in the same manner as solution C, and the solvent for obtaining solution G is also determined in the same manner as solution C.

[0037] For example, the light absorbing composition can be prepared by adding an alkoxysilane while mixing the liquid D and the liquid H in a predetermined ratio, and adding a curable resin such as a silicone resin, if necessary. In this case, the dialkoxysilane may be added after mixing the liquid D and the liquid H.

[0038] As shown in FIG. 1, the optical filter 1a includes a light absorbing layer 10. The light absorbing layer 10 contains a light absorbent and a hydrolysis condensate of alkoxysilane. The light absorbing layer 10 is characterized by its flexibility. For example, when one main surface 10a of the light absorbing layer 10 is measured according to a nanoindentation method (continuous stiffness measurement method) using a nanoindenter, the average Young's modulus is 2.00 GPa or less. The average Young's modulus may be, for example, 0.10 to 2.00 GPa. Furthermore, the average hardness is 0.06 GPa or less. The average hardness may be 0.005 to 0.06 GPa. In this way, the light absorbing layer 10 has a desired flexibility while including a skeleton having a siloxane bond due to the hydrolysis condensate of alkoxysilane. For details of the nanoindentation method (continuous stiffness measurement method), reference can be made to International Publication No. 2019 / 044758 and Japanese Patent Application Laid-Open No. 2015-174270.

[0039] The hydrolysis condensation product of alkoxysilane contained in the light absorbing layer 10 includes, for example, a hydrolysis condensation product of dialkoxysilane, which provides the light absorbing layer 10 with desired flexibility.

[0040] From another viewpoint, the light absorbing layer 10 may be formed of, for example, a cured product of the light absorbing composition described above. In this case, the light absorbing layer 10 is likely to have the desired flexibility.

[0041] When a moisture resistance test is performed in which the optical filter 1a is kept in an environment of 85°C and 85% relative humidity for 1000 hours, the optical filter 1a satisfies, for example, the following conditions. In this case, the optical filter 1a exhibits good moisture resistance. With respect to each parameter, the "amount of change" refers to the absolute value of the difference in the parameter value before and after the moisture resistance test. The "amount of change in average transmittance" refers to the absolute value of the difference between the average value of the transmittance before the moisture resistance test and the average value of the transmittance after the moisture resistance test in a specified wavelength range. The "amount of change in maximum transmittance" refers to the absolute value of the difference between the maximum value of the transmittance before the moisture resistance test and the maximum value of the transmittance after the moisture resistance test in a specified wavelength range. The unit of the amount of change in a parameter related to transmittance expressed as a percentage is represented as "points." (i) Change in average transmittance at wavelengths of 450 to 600 nm ΔT 450-600 is 3 points or less. ΔT 450-600 is preferably 1 point or less, and more preferably 0.5 point or less. (ii) The change in UV cutoff wavelength Δλuvc is 5 nm or less, and the change in IR cutoff wavelength Δλirc is 5 nm or less. The UV cutoff wavelength is a wavelength having a transmittance of 50% in the wavelength range of 350 nm to 450 nm. The IR cutoff wavelength is a wavelength having a transmittance of 50% in the wavelength range of 600 nm to 800 nm. (iii) The change in the value obtained by subtracting the UV cutoff wavelength from the IR cutoff wavelength, Δλirc-uvc, is 10 nm or less. (iv) Change in maximum transmittance at wavelengths of 300 to 350 nm ΔT max300-350 is less than 1 point. max300-350 is preferably 0.5 points or less. (v) Change in maximum transmittance ΔT at wavelengths of 300 to 360 nm max300-360 is less than 1 point. max300-360 is preferably 0.5 points or less. (vi) Change in average transmittance at wavelengths of 700 to 750 nm, ΔT AVE700-750 is less than or equal to 3 points. AVE700-750 is preferably 1 point or less. (vii) Change in maximum transmittance ΔT at wavelengths from 750 to 1080 nm max750-1080 is less than or equal to 3 points. max750-1080 is preferably 1 point or less. (viii) The change in maximum transmittance at wavelengths of 800 to 950 nm, ΔT max800-950 , the change in maximum transmittance at wavelengths of 800 to 1000 nm ΔT max800-1000 , the change in maximum transmittance at wavelengths of 800 to 1050 nm ΔT max800-1050 , the change in maximum transmittance at wavelengths of 800 to 1100 nm ΔT max800-1100 , the change in maximum transmittance at wavelengths of 800 to 1150 nm ΔT max800-1150, and the change in maximum transmittance ΔT at wavelengths of 800 to 1200 nm max800-1200 Each of these is 3 points or less. max800-950 , ΔT max800-1000 , ΔT max800-1050 , ΔT max800-1100 , ΔT max800-1150 , and ΔT max800-1200 Each of these is preferably 1 point or less.

[0042] As shown in Fig. 1, the optical filter 1a is, for example, composed of a single light absorbing layer 10. In this case, the optical filter 1a is used, for example, separately from an imaging element or an optical component. The optical filter 1a may be bonded to the imaging element and the optical component. On the other hand, the optical filter 1a may be constructed by applying the above-mentioned light absorbing composition to the imaging element or the optical component and curing the light absorbing composition.

[0043] The optical filter 1a can be produced, for example, by peeling off the light absorbing layer 10 formed on a substrate from the substrate. In this case, the material of the substrate may be glass, resin, or metal. The surface of the substrate may be subjected to a surface treatment such as coating with a fluorine-containing compound.

[0044] The optical filter 1a may be modified, for example, to the optical filter 1b shown in FIG. 2. The optical filter 1b is configured similarly to the optical filter 1a unless otherwise specified. The components of the optical filter 1b that are the same as or correspond to the components of the optical filter 1a are given the same reference numerals, and detailed description is omitted. The description of the optical filter 1a also applies to the optical filter 1b as long as there is no technical contradiction.

[0045] 2, the optical filter 1b includes a light absorbing layer 10 and a transparent dielectric substrate 20. The light absorbing layer 10 is formed parallel to one of the main surfaces of the transparent dielectric substrate 20. The light absorbing layer 10 may be in contact with one of the main surfaces of the transparent dielectric substrate 20, for example. In this case, the light absorbing layer 10 is formed, for example, by applying the above-mentioned light absorbing composition to one of the main surfaces of the transparent dielectric substrate 20 and curing the light absorbing composition.

[0046] The type of the transparent dielectric substrate 20 is not limited to a specific type. The transparent dielectric substrate 20 may have an absorption ability in the infrared region. The transparent dielectric substrate 20 may have an average spectral transmittance of 90% or more at wavelengths of, for example, 350 nm to 900 nm. The material of the transparent dielectric substrate 20 is not limited to a specific material, but may be, for example, a specific glass or resin. When the material of the transparent dielectric substrate 20 is glass, the transparent dielectric substrate 20 is, for example, transparent glass or infrared cut glass made of silicate glass such as soda-lime glass and borosilicate glass. The infrared cut glass is, for example, phosphate glass or fluorophosphate glass containing CuO.

[0047] When the material of the transparent dielectric substrate 20 is a resin, the resin is, for example, a cyclic olefin resin such as a norbornene resin, a polyarylate resin, an acrylic resin, a modified acrylic resin, a polyimide resin, a polyetherimide resin, a polysulfone resin, a polyethersulfone resin, a polycarbonate resin, or a silicone resin.

[0048] Each of the optical filters 1a and 1b may be modified to further include other functional films, such as an infrared reflective film. EXAMPLES

[0049] The present invention will be described in more detail with reference to examples, but the present invention is not limited to the following examples.

[0050] <Example 1> (Preparation of aryl-based copper phosphonates) 4.500g of copper acetate monohydrate and 240g of tetrahydrofuran (THF) were mixed and stirred for 3 hours to obtain a copper acetate solution. Next, 1.646g of Plysurf A208N (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), a phosphate ester compound, was added to the obtained copper acetate solution and stirred for 30 minutes to obtain solution A. 40g of THF was added to 0.706g of phenylphosphonic acid and stirred for 30 minutes to obtain solution B-1. 4.230g of 4-bromophenylphosphonic acid was added to 40g of THF and stirred for 30 minutes to obtain solution B-2. Next, the B-1 liquid and the B-2 liquid were mixed and stirred for 1 minute, and 8.664 g of methyltriethoxysilane (MTES) (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KBE-13) and 2.830 g of tetraethoxysilane (TEOS) (manufactured by Kishida Chemical Co., Ltd., special grade) were added to this mixed liquid, and further stirred for 1 minute to obtain a B liquid. While stirring the A liquid, the B liquid was added to the A liquid, and stirred for 1 minute at room temperature. Next, 140 g of toluene was added to this solution, and stirred for 1 minute at room temperature to obtain a C liquid. This C liquid was put into a flask and heated in an oil bath (manufactured by Tokyo Rikakikai Co., Ltd., model: OSB-2100), and a desolvation treatment was performed using a rotary evaporator (manufactured by Tokyo Rikakikai Co., Ltd., model: N-1110SF). The set temperature of the oil bath was adjusted to 105°C. Then, the D liquid according to Example 1 after the desolvation treatment was taken out from the flask. The solvent was not completely removed during the solvent removal process, but was removed so that the viscosity was reduced to a certain degree. In this way, liquid D, which is a dispersion of aryl-based copper phosphonate (UV-IR absorbent), was obtained.

[0051] (Preparation of Alkyl Phosphonic Copper) 4.500g of copper acetate monohydrate and 240g of THF were mixed and stirred for 3 hours to obtain a copper acetate solution. Next, 2.572g of Plysurf A208N, a phosphate ester compound, was added to the obtained copper acetate solution and stirred for 30 minutes to obtain liquid E. In addition, 40g of THF was added to 2.886g of n-butylphosphonic acid and stirred for 30 minutes to obtain liquid F. Liquid E was added to liquid E while stirring, and stirred at room temperature for 1 minute. Next, 100g of toluene was added to this solution, and stirred at room temperature for 1 minute to obtain liquid G. This liquid G was placed in a flask and heated in an oil bath, and a solvent removal treatment was performed using a rotary evaporator. The set temperature of the oil bath was adjusted to 105°C. Then, liquid H according to Example 1 after the solvent removal treatment was taken out of the flask. The solvent removal treatment was performed so that the viscosity of liquid H was reduced to a certain degree without completely removing the solvent in the solvent removal treatment. In this way, liquid H, which is a dispersion of copper butylphosphonate (IR absorbent), was obtained.

[0052] (Preparation of Light-Absorbing Composition) 12.57 g of silicone resin (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KR-300) was added to the D liquid, and the mixture was stirred for 30 minutes to obtain the I liquid. An amount equivalent to 40 mass % of the total amount of the H liquid was added to the I liquid, and 10.840 g of alkoxysilane methyltriethoxysilane (MTES) (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KBE-13), 5.660 g of tetraethoxysilane (TEOS) (manufactured by Kishida Chemical Co., Ltd., special grade), and 4.896 g of dimethyldiethoxysilane (DMDES) (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KBE-22) were further added thereto, and the mixture was stirred for 30 minutes to obtain the light absorbing composition according to Example 1. Assuming that a complete hydrolysis condensation product of the alkoxysilane is obtained, the light absorbing composition according to Example 1 was prepared so that the content of the MTES-derived silane compound in the complete hydrolysis condensation product of the alkoxysilane is 60.0%, the content of the TEOS-derived silane compound is 20.0%, and the content of the DMDES-derived silane compound is 20.0% by mass in the complete hydrolysis condensation product of the alkoxysilane. The calculation was performed under the assumption that the ratio of the amount of the MTES-derived silane compound (solid content) present in the complete hydrolysis condensation product of the alkoxysilane to the amount of the MTES added is 37.64% by mass, the ratio of the amount of the TEOS-derived silane compound (solid content) present in the complete hydrolysis condensation product of the alkoxysilane to the amount of the TEOS added is 28.84% by mass, and the ratio of the amount of the DMDES-derived silane compound (solid content) present in the complete hydrolysis condensation product of the alkoxysilane to the amount of the DMDES added is 50.01% by mass. The calculation was performed under the same assumption in Examples 2 and 3 and Comparative Example 1. Table 2 shows the relationship between the amount of alkoxysilane added in the preparation of Solution D and the preparation of the light absorbing composition.

[0053] (Fabrication of optical filters) 0.1 g of a surface antifouling coating agent (manufactured by Daikin Industries, product name: Optool DSX, concentration of active ingredient: 20% by mass) and 19.9 g of a hydrofluoroether-containing liquid (manufactured by 3M, product name: Novec 7100) were mixed and stirred for 5 minutes to prepare a fluorine treatment agent (concentration of active ingredient: 0.1% by mass). This fluorine treatment agent was poured onto a circular borosilicate glass (manufactured by SCHOTT, product name: D263 T eco) with a diameter of 200 mm and a thickness of 0.7 mm. The glass substrate was then left at room temperature for 24 hours to dry the coating of the fluorine treatment agent, and the glass surface was then lightly wiped with a dust-free cloth containing Novec 7100 to remove excess fluorine treatment agent. In this way, a fluorine-treated substrate was produced.

[0054] The light-absorbing composition according to Example 1 was applied onto a fluorine-treated substrate using a dispenser. At this time, a stainless steel mold (internal dimensions: about 100 mm square) was used to apply the coating film so that the coating film could maintain a sufficient thickness. The substrate on which the light-absorbing composition was applied was left to stand for a predetermined time to sufficiently promote the reaction of the components of the light-absorbing composition, and then the substrate was slowly heated from room temperature to slowly evaporate the solvent, while hardening the light-absorbing composition. The maximum temperature reached during this heating was adjusted to 85°C. Furthermore, the substrate was left in an environment of a temperature of 85°C and a relative humidity of 85% for about 2 hours to promote the hydrolysis reaction of the alkoxysilane, and a light-absorbing film was obtained. The end of the light-absorbing film thus obtained was lifted and peeled off from the substrate, and an optical filter according to Example 1 having a size of about 100 mm square in a plan view was obtained.

[0055] (Cutting optical filters) The optical filter according to Example 1 was cut into strips using a rotary cutter (manufactured by Olfa Corporation) having a circular blade with a diameter of 28 mm. Specifically, a load of about 30 N was applied to the optical filter along four straight lines that were parallel to one side of the optical filter and spaced 20 mm apart, to cut the optical filter. The obtained strip-shaped sample was observed at a magnification of 50 times using a metal microscope. As a result, it was confirmed that no damage such as cracks or breaks occurred around the cut surface of the sample, and that the optical filter according to Example 1 was cut well.

[0056] <Example 2> In the same manner as in Example 1, D liquid, which is a dispersion of aryl-based copper phosphonate (UV-IR absorbent), and H liquid, which is a dispersion of butylphosphonate copper (IR absorbent), were obtained. Next, 12.57 g of silicone resin (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KR-300) was added to D liquid, and the mixture was stirred for 30 minutes to obtain I liquid. An amount equivalent to 40 mass % of the total amount of H liquid was added to I liquid, and alkoxysilanes methyltriethoxysilane (MTES) (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KBE-13) 5.420 g, tetraethoxysilane (TEOS) (Kishida Chemical Co., Ltd., special grade) 2.830 g, and dimethyldiethoxysilane (DMDES) (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KBE-22) 2.448 g were added thereto, and the mixture was stirred for 30 minutes to obtain a light absorbing composition according to Example 2. Assuming that a complete hydrolysis condensation product of the alkoxysilane is obtained, the light-absorbing composition of Example 2 was prepared so that the content of the MTES-derived silane compound in the complete hydrolysis condensation product of the alkoxysilane is 65.0%, the content of the TEOS-derived silane compound is 20.0%, and the content of the DMDES-derived silane compound is 15.0%, based on mass.

[0057] An optical filter according to Example 2 was produced in the same manner as in Example 1, except that the light absorbing composition according to Example 2 was used instead of the light absorbing composition according to Example 1. In addition, the optical filter according to Example 2 was cut into strips in the same manner as the optical filter according to Example 1. The obtained strip-shaped sample was observed at a magnification of 50 times using a metal microscope. As a result, it was confirmed that no damage such as cracks or breaks occurred around the cut surface of the sample, and the optical filter according to Example 2 was cut well.

[0058] <Example 3> In the same manner as in Example 1, D liquid, which is a dispersion of aryl-based copper phosphonate (UV-IR absorbent), and H liquid, which is a dispersion of butyl copper phosphonate (IR absorbent), were obtained. Next, 12.57 g of silicone resin (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KR-300) was added to D liquid, and the mixture was stirred for 30 minutes to obtain I liquid. An amount equivalent to 40 mass % of the total amount of H liquid was added to I liquid, and 7.344 g of alkoxysilane dimethyldiethoxysilane (DMDES) (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KBE-22) was further added thereto, and the mixture was stirred for 30 minutes to obtain a light absorbing composition according to Example 3. In the preparation of the light absorbing composition according to Example 3, methyltriethoxysilane (MTES) and tetraethoxysilane (TEOS) were not added to the mixture of I liquid and H liquid. Assuming that a complete hydrolysis condensation product of the alkoxysilane is obtained, the light-absorbing composition of Example 3 was prepared so that the content of the MTES-derived silane compound in the complete hydrolysis condensation product of the alkoxysilane is 42.1%, the content of the TEOS-derived silane compound is 10.5%, and the content of the DMDES-derived silane compound is 47.4%, by mass.

[0059] An optical filter according to Example 3 was produced in the same manner as in Example 1, except that the light absorbing composition according to Example 3 was used instead of the light absorbing composition according to Example 1. In addition, the optical filter according to Example 3 was cut into strips in the same manner as the optical filter according to Example 1. The obtained strip-shaped sample was observed at a magnification of 50 times using a metal microscope. As a result, it was confirmed that no damage such as cracks or breaks occurred around the cut surface of the sample, and the optical filter according to Example 3 was cut well.

[0060] <Comparative Example 1> In the same manner as in Example 1, D liquid, which is a dispersion of aryl-based copper phosphonate (UV-IR absorbent), and H liquid, which is a dispersion of butyl copper phosphonate (IR absorbent), were obtained. Next, 12.57 g of silicone resin (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KR-300) was added to D liquid, and the mixture was stirred for 30 minutes to obtain I liquid. An amount equivalent to 40 mass % of the total amount of H liquid was added to I liquid, and the mixture was stirred for another 30 minutes to obtain a light-absorbing composition according to Comparative Example 1. In the preparation of the light-absorbing composition according to Comparative Example 1, no alkoxysilane was added to the mixture of I liquid and H liquid.

[0061] An optical filter according to Comparative Example 1 was produced in the same manner as in Example 1, except that the light-absorbing composition according to Comparative Example 1 was used instead of the light-absorbing composition according to Example 1. In addition, an attempt was made to cut the optical filter according to Comparative Example 1 into strips in the same manner as the optical filter according to Example 1. However, a large number of cracks were generated around four straight lines parallel to one side of the optical filter and located at intervals of 20 mm, and the optical filter according to Comparative Example 1 could not be cut well, and no strip-shaped sample was obtained.

[0062] <Transmittance spectrum measurement> The transmittance spectrum of each optical filter was measured at an incident angle of 0° using an ultraviolet-visible-near infrared spectrophotometer (manufactured by JASCO Corporation, product name: V-670). The transmittance spectra of the optical filters according to Example 1, Example 2, Example 3, and Comparative Example 1 are shown in Figures 3, 4, 5, and 6, respectively. Table 1 shows the characteristics related to the transmittance read from Figures 3 to 6.

[0063] <Thickness measurement> The thickness of the optical filter was measured by measuring the distance from the surface of the optical filter using a laser displacement meter (Keyence Corporation, product name: LK-H008). The results are shown in Table 1.

[0064] <Young's modulus and hardness> Using a nanoindenter (manufactured by MTS Systems, product name: Nano Indenter XP), the surface of the optical filter was measured according to the nanoindentation method (continuous stiffness measurement method). A triangular pyramidal indenter made of diamond was used as the indenter, and the measurement was performed at room temperature of about 23°C and in the atmosphere. The hardness values ​​in the indentation depth range of 5 to 10 μm in the hardness-indentation depth diagram obtained by this measurement were averaged to determine the average hardness of the surface of each optical filter. In addition, the Young's modulus values ​​in the indentation depth range of 5 to 10 μm in the Young's modulus-indentation depth diagram obtained by this measurement were averaged to determine the average Young's modulus of each optical filter. In addition, considering that the main component of the optical filter is silicone resin, the Poisson's ratio of the optical filter was set to 0.4. The results are shown in Table 3. In the examples, the average Young's modulus was 0.87 to 1.6 GPa, and the average hardness was 0.020 to 0.048 GPa. On the other hand, in the comparative example, the average Young's modulus was 2.6 GPa, and the hardness was 0.11 GPa, making it clear that the flexibility was poor.

[0065] <Haze measurement> Using a haze meter (manufactured by Murakami Color Research Laboratory, product name: HM-65L2), the haze of the optical filters according to Examples 1 to 3 and the optical filter according to Comparative Example 1 was measured in accordance with Japanese Industrial Standard JIS K 7136. The results are shown in Table 3.

[0066] <Moisture resistance test> The optical filters according to Examples 1 to 3 were stored for 1000 hours in a thermohygrostat (Tokyo Rikakikaisha, KCL-2000A) set at a temperature of 85°C and a relative humidity of 85%, and a moisture resistance test was performed. Using an ultraviolet-visible-near infrared spectrophotometer (JASCO Corporation, product name: V-670), the transmittance spectrum at an incident angle of 0° of the optical filters according to Examples 1 and 2 after the moisture resistance test was measured. The results are shown in Figs. 7 and 8. In Figs. 7 and 8, the solid line indicates the transmittance spectrum of the optical filter before the moisture resistance test, and the dashed line indicates the transmittance spectrum of the optical filter after the moisture resistance test. The values ​​of each parameter read from these transmittance spectra are shown in Table 4. Note that the optical filter according to Example 3 after the moisture resistance test was cloudy and did not transmit any light.

[0067] As shown in Table 3, it was suggested that the optical filters according to Examples 1 to 3 have higher flexibility than the optical filter according to Comparative Example 1. Furthermore, as shown in Table 4, it was suggested that the optical filters according to Examples 1 and 2 satisfy the above conditions (i) to (viii) and have good moisture resistance.

[0068] The light absorbing film of the optical filter according to the embodiment of the present invention has a small Young's modulus and high flexibility. Therefore, after the light absorbing film is formed on a flat substrate, the light absorbing film peeled off from the substrate is laminated on the surface of another base material having an arbitrary curved surface or a highly flexible flat surface, such as a lens, a flexible filter, a highly flexible resin filter, or other optical element, so that the light absorbing film can be laminated on the curved surface with a uniform thickness, thereby forming an optical element or optical filter having a light absorbing function.

[0069] In addition, in recent years, highly flexible substrates, such as displays using organic electroluminescence, are often used in portable communication devices such as smartphones. The light absorbing film according to the embodiment of the present invention exhibits conformability to such flexible displays and panels as a substrate, and is therefore easily applicable to these fields.

[0070] In general coating methods such as spin coating or dip coating, it is difficult to form a film of uniform thickness on a curved surface because very precise control is required. On the other hand, the above method is very effective because it is relatively easy to form a light absorbing film of uniform thickness on a curved surface.

[0071] An adhesive may be used to attach the light absorbing film to the curved surface. The film after the pre-baking may be laminated while conforming to the curved surface of the substrate, and then a heat treatment or a heat and humidification treatment may be performed. In the latter case, the pre-baking temperature is preferably 60°C or less, and the final heating and humidification temperatures are preferably 80°C or more.

[0072] Furthermore, as the substrate on which the light absorbing film is to be produced, a substrate on which wires made of glass fiber, carbon fiber, cellulose nanofiber, or the like are formed (for example, in a lattice shape) on the surface may be used. In this case, after the light absorbing film is formed on the substrate, it is peeled off together with the wires to obtain a light absorbing film with the wires formed inside or on the surface. Such wires impart appropriate mechanical rigidity to the light absorbing film, so that a light absorbing film having flexibility and rigidity can be produced.

[0073] Furthermore, after forming a coating film on a flat substrate, the substrate may be heated while being deformed, or heated and humidified, to form a light-absorbing film in a special surface state (e.g., lens-like) that matches the final shape of the substrate. By deforming or curing the light-absorbing film to match the desired shape of the substrate, light-absorbing filters with various surface states (flat or curved) can be produced.

[0074] The light absorbing film according to the embodiment of the present invention is also excellent in impact resistance. Therefore, it has the advantage of being less subject to restrictions in the environment in which it is used. The light absorbing film according to the embodiment of the present invention can be effectively used in, for example, a wearable device that is exposed to long-term vibration and strong impact, particularly a camera module, an optical sensor, or a part of various optical systems built into a wearable camera or action camera.

[0075]

Table 1

[0076]

Table 2

[0077]

Table 3

[0078]

Table 4

Claims

1. A light absorbing layer including a light absorbing compound and a resin, the light absorbing layer has an average Young's modulus of 2.00 GPa or less and an average hardness of 0.06 GPa or less, as measured by a nanoindentation method (continuous stiffness measurement method); Optical filters.

2. The light absorbing layer contains at least one selected from the group consisting of a hydrolyzate of an alkoxysilane and a polymer of a hydrolyzate of an alkoxysilane. The optical filter of claim 1 .

3. The alkoxysilane includes at least one selected from the group consisting of dialkoxysilane, tetraalkoxysilane, and trialkoxysilane. The optical filter of claim 2 .

4. The mass ratio of the dialkoxysilane to the alkoxysilane is 15 to 48%, when the alkoxysilane is converted into a completely hydrolyzed condensate. The optical filter according to claim 3 .

5. The light absorbing compound includes a copper component and a phosphonic acid. The optical filter according to any one of claims 1 to 4.

6. The optical filter has a first transmittance spectrum and a second transmittance spectrum for an incident angle of 0° before and after a humidity resistance test in which the optical filter is held in an environment at a temperature of 85° C. and a humidity of 85% for 1000 hours, respectively, and the first transmittance spectrum and the second transmittance spectrum satisfy the following (i), (ii), and (iii): The optical filter according to any one of claims 1 to 5. (i) A change amount ΔT which is an absolute value of the difference between the average transmittance of the first transmittance spectrum in a wavelength range of 450 nm to 600 nm and the average transmittance of the second transmittance spectrum in a wavelength range of 450 nm to 600 nm. 450-600 is less than 3 points. (ii) A change in UV cutoff wavelength Δλ, which is the absolute value of the difference between the wavelength at which the transmittance of the first transmittance spectrum is 50% in the wavelength range of 350 nm to 450 nm and the wavelength at which the transmittance of the second transmittance spectrum is 50% in the wavelength range of 350 nm to 450 nm. uvc is 5 nm or less, and is the absolute value of the difference between the wavelength at which the transmittance of the first transmittance spectrum is 50% in the wavelength range of 600 nm to 800 nm and the wavelength at which the transmittance of the second transmittance spectrum is 50% in the wavelength range of 600 nm to 800 nm. irc is 5 nm or less. (iii) a change amount Δλ, which is the absolute value of the difference between the value obtained by subtracting the UV cutoff wavelength from the IR cutoff wavelength in the first transmittance spectrum and the value obtained by subtracting the UV cutoff wavelength from the IR cutoff wavelength in the second transmittance spectrum; irc-uvc is 10 nm or less.

7. The first transmittance spectrum and the second transmittance spectrum satisfy the following (iv), (v), (vi), and (vii): The optical filter according to claim 6 . (iv) A change amount ΔT, which is the absolute value of the difference between the maximum transmittance of the first transmittance spectrum in a wavelength range of 300 nm to 350 nm and the maximum transmittance of the second transmittance spectrum in a wavelength range of 300 nm to 350 nm. max300-350 is less than 1 point. (v) A change amount ΔT, which is the absolute value of the difference between the maximum transmittance of the first transmittance spectrum in a wavelength range of 300 nm to 360 nm and the maximum transmittance of the second transmittance spectrum in a wavelength range of 300 nm to 360 nm. max300-360 is less than 1 point. (vi) A change amount ΔT, which is an absolute value of the difference between the average transmittance of the first transmittance spectrum in a wavelength range of 700 nm to 750 nm and the average transmittance of the second transmittance spectrum in a wavelength range of 700 nm to 750 nm. AVE700-750 is less than 3 points. (vii) A change amount ΔT, which is an absolute value of the difference between the maximum transmittance of the first transmittance spectrum in a wavelength range of 750 nm to 1080 nm and the maximum transmittance of the second transmittance spectrum in a wavelength range of 750 nm to 1080 nm. max750-1080 is less than 3 points.

8. A light absorbing composition including a light absorbing compound, a curable resin, and at least one selected from the group consisting of an alkoxysilane and an alkoxysilane hydrolysate is applied to a surface of a flat substrate to form a coating film; and curing the coating film to form a light absorbing layer. A method for manufacturing an optical filter.

9. further comprising peeling the light absorbing layer from the substrate. A method for producing the optical filter according to claim 8 .

10. Further, the method includes laminating the light absorbing layer on a surface including a curved surface of the substrate. A method for producing the optical filter according to claim 9.

11. the light absorbing layer has an average Young's modulus of 2.00 GPa or less and an average hardness of 0.06 GPa or less, as measured by a nanoindentation method (continuous stiffness measurement method); A method for producing the optical filter according to claim 9.

12. The alkoxysilane includes at least one selected from the group consisting of dialkoxysilane, tetraalkoxysilane, and trialkoxysilane. A method for producing the optical filter according to any one of claims 8 to 11.

13. The mass ratio of the dialkoxysilane to the alkoxysilane is 15 to 48%, when the alkoxysilane is converted into a completely hydrolyzed condensate. A method for producing the optical filter according to claim 12.